“The Art of the Court” in the Long Middle Ages – A String of Renaissances - Jurković, Miljenko; Josipović, Ivan (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
From Late Antiquity to the Renaissance, forms and ideas of Antiquity were repeatedly used in monumental arts, in arts and crafts (along with all artistic forms such as literature, music along with philosophy…). It seems that Antiquity, not only Classical Antiquity, but mere Christian Antiquity, was never neglected or forgotten to be reinvented in the period we call the Renaissance. We can really enumerate so many renaissances from the 4th to the 15th century, all of them being part of the arts of the elites – the art of the court. In this paper, I am trying to affirm the term of court art as the carrier of numerous medieval renaissances in European art of the Middle Ages.